Serotonin Transporter Defect Disturbs Structure and Function of the Auditory Cortex in Mice - Pan, Wenlu; Pan, Jing; Zhao, Yan; Zhang, Hongzheng; Tang, Jie (Frontiers in Neuroscience, 2021)
Serotonin transporter (SERT) modulates the level of 5-HT and significantly affects the activity of serotonergic neurons in the central nervous system. The manipulation of SERT has lasting neurobiological and behavioral consequences, including developmental dysfunction, depression and anxiety. Auditory disorders have been widely reported as the adverse events of these mental diseases. It is unclear how SERT impacts neuronal connections/interactions and what mechanism(s) may elicit the disruption of normal neural network functions in auditory cortex. In the present study, we report on the neuronal morphology and function of auditory cortex in SERT knockout mice. We show that the dendritic length of the forth layer (L-IV) pyramidal neurons and the second-third layer (L-II/III) interneurons were reduced in the auditory cortex of the SERT KO mice. The number and density of dendritic spines of these neurons were significantly less than that of wild-type neurons. Also, the frequency tonotopic organization of primary auditory cortex was disrupted in SERT KO mice. The auditory neurons of SERT KO mice exhibit border frequency tuning with high intensity thresholds. These findings indicate that SERT plays a key role in development and functional maintenance of auditory cortical neurons. Auditory function should be examined when SERT is selected as a target in the treatment for psychiatric disorders.